Carglumic Acid Contributes to a Favorable Clinical Course in a Case of Severe Propionic Acidemia - Jun Kido; Shirou Matsumoto; Kimitoshi Nakamura (Case Reports in Pediatrics)
Propionic acidemia (PA) is manifested as an abnormal accumulation of propionic acid and its metabolites, including methylcitrate, 3-hydroxypropionic acid, and propionylglycine, and is caused by a defect of propionyl-CoA carboxylase. PA is complicated by acute life-threatening metabolic crises, which are precipitated by a catabolic state and result in multiple organ failure or even death, if untreated. A neonate with PA recovered from the first metabolic crisis 3 days after birth but developed a second metabolic crisis during the recovery phase. This patient was considered to have severe PA and was accordingly given carglumic acid treatment in combination with carnitine supplementation and protein restriction, which was expected to prevent a recurrent metabolic attack. The patient did not develop hyperammonemia after receiving carglumic acid and was never hospitalized. Moreover, she did not present with acidosis even during viral infection. At 26 months of age, she led a stable life while receiving carglumic acid and regular rehabilitation. Carglumic acid treatment in combination with carnitine supplementation and protein restriction prevented metabolic decompensation, which would have otherwise required hospitalization, and resulted in improved quality of life and developmental outcomes.